2017
DOI: 10.7567/jjap.56.067001
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductance change of graphene-based devices upon surface modification for detecting botulinum neurotoxin

Abstract: We report an electric conductance change in a graphene-based device upon molecular adsorption for detecting botulinum neurotoxin (BoNT) using the antibody–antigen binding strategy. This device consists of a 400-µm-wide monolayer of graphene between the source and drain electrodes. As-fabricated devices exhibit p-type behaviors. After modifying graphene with linkers and antibodies, BoNT detection was performed by dropping a target solution and measuring the conductance change of the devices. The immobilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…It was observed that the more negatively charged antibody layer would p-dope the graphene layer further, resulting in a larger I SD at V G = 0, whereas the positively charged BoNT layer caused a I SD drop at V G = 0 due to ndoping caused by the electrostatic gating effect. This GFET biosensor was able to show a normalized current change of 7% caused by the antibody-BoNT binding regime, an improvement from the 1% response demonstrated previously for AlGaN/GaN electrical sensors (Kim et al, 2017).…”
Section: Applications In Food Adulterants and Toxicants Detectionsupporting
confidence: 52%
See 3 more Smart Citations
“…It was observed that the more negatively charged antibody layer would p-dope the graphene layer further, resulting in a larger I SD at V G = 0, whereas the positively charged BoNT layer caused a I SD drop at V G = 0 due to ndoping caused by the electrostatic gating effect. This GFET biosensor was able to show a normalized current change of 7% caused by the antibody-BoNT binding regime, an improvement from the 1% response demonstrated previously for AlGaN/GaN electrical sensors (Kim et al, 2017).…”
Section: Applications In Food Adulterants and Toxicants Detectionsupporting
confidence: 52%
“…A primary motivator for using graphene in biosensing platforms is the simplicity in chemical functionalization (Novoselov et al, 2012). A variety of bioreceptors can be added to the surface of graphene which bind selectively to target analytes; aptamers (Xu et al, 2019), antibodies (Kim et al, 2017) and DNA (Liu et al, 2018b) are some examples of the bioreceptors used to functionalize the surface of graphene field effect transistors (GFETs) biosensors. Bi-functional molecules such as 1-pyrenebutyric acid N-hydroxysuccinimide ester (PBASE) can be used to facilitate the non-covalent functionalization of graphene at the pyrene end and the immobilization of bioreceptors at the N-hydroxysuccinimide ester end (Chen et al, 2001).…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…101) Kim et al reported that a graphene-based device could be used to detect the molecular absorption of botulinum neurotoxin that consists of approximately 150k base-pair (bp) proteins. 102) With the immobilization of linkers of antibody-antigen binding sites on the graphene transistor, the electrical conductance of the transistor was modified by the adsorption of antibody proteins. 102) Fig.…”
Section: Sensing Of Coronavirus With Nanomaterialsmentioning
confidence: 99%